2001
DOI: 10.1097/00003246-200102000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nosocomial pneumonia in critically ill trauma patients

Abstract: It seems that factors related to the patient's clinical course, rather than variables registered on the first days of ICU admission, are those that would exert an influence on the development of nosocomial pneumonia in critically ill trauma patients. In this way, from our point of view, in our study the main risk factors are the use of prolonged mechanical ventilation (>4 hrs) and positive end-expiratory pressure. At the same time, we can conclude that the reduction of this infection incidence could decrease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(56 citation statements)
references
References 31 publications
7
41
0
5
Order By: Relevance
“…This finding is consistent with reports of other outbreaks [6,29,33,34]. But there was no significant diference between non survivors and survivors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with reports of other outbreaks [6,29,33,34]. But there was no significant diference between non survivors and survivors.…”
Section: Discussionsupporting
confidence: 92%
“…baumannii outbreaks have been reported previously, particularly in ICU wards [22][23][24][25][26]. Severe underlying diseases, invasive diagnostic and therapeutic procedures used in ICUs have been demonstrated to predispose patients to severe infections with A. baumannii [27][28][29]. Our results show that nosocomial infections and colonizations by A. baumannii in the ICU were prolonged for several months.…”
Section: Discussionsupporting
confidence: 61%
“…[6][7][8][9] ), with the most common rate being approximately 46% (ref. 2,18 ). However, comparison of mortality data is limited by the fact that varied approaches are used to report the data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Forel et al 19 assessed icU mortality in two Vap subgroups, 28-day (27%) and 90-day (41%) rates, whereas Werarak reported a 30-day mortality rate of 46% (ref. 20 ) and Tejada et al stated 46% mortality with no time period specified 18 . a study by esperatti et al described a group of 315 icU patients and found in-hospital mortality rates 36% for Hap and 42% for Vap (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia gladioli 1 1 (Wilsher, Kolbe et al 1997;Otterbein, Splettstoesser et al 1998;Clode, Metherell et al 1999;Segonds, Heulin et al 1999;Segonds and Chabanon 2001) Burkholderia species 1 1 (Otterbein, Splettstoesser et al 1998;Segonds, Heulin et al 1999;Segonds and Chabanon 2001) Chryseomonas luteola 1 (Hawkins, Moriarty et al 1991;Ndugulile, Jureen et al 2005) Citrobacter freundii 1 (Hodges, Degener et al 1978;Tejada Artigas, Bello Dronda et al 2001;Fiorio, Marroni et al 2004;Ndugulile, Jureen et al 2005) Comamonas acidovrans Diptheroids 1 (Schofferman, Zucherman et al 1991) Enterobacter agglomerans 1 (Geere 1977;Goldmann, Dixon et al 1978;Maki 1981;Astagneau, Gottot et al 1994) Escherichia coli 1 1 (Hoogkamp-Korstanje, Cats et al 1982;Newman 2002;Larson, Cimiotti et al 2005;Kramer, Schwebke et al 2006;Toniolo, Endimiani et al 2006) Flavimonas oryzihabitans 1 1 (Hawkins, Moriarty et al 1991) Flavobacterium meningosepticum 1 1 (Abrahamsen, Finne et al 1989;Liu, Wong et al 1999;Bellais, Girlich et al 2002;Seetha, Bairy et al 2002) Flavobacterium breve 1 1 (Bellais, Girlich et al 2002) Gram (+) cocci 1 (Peter, Jehl et al 1988;…”
Section: Referencesmentioning
confidence: 99%